2019
DOI: 10.3389/fmicb.2018.03312
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Fermentation With Enterococcus mundtii QAUSD01 and Wickerhamomyces anomalus QAUWA03 Consortia Induces Concurrent Gliadin and Phytic Acid Degradation and Inhibits Gliadin Toxicity in Caco-2 Monolayers

Abstract: Foods containing high amounts of either phytic acid or gliadin can pose a risk for development of iron deficiency and celiac disease, respectively. The present study was conducted to evaluate the effects of preselected gliadin degrading strains, Enterococcus mundtii QAUSD01 and Wickerhamomyces anomalus QAUWA03, on phytic acid and gliadin degradation in six wheat cultivars ( Lasani 2008 , Seher 2006 , Chakwal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Consistent with our findings, other authors have also reported the ability of W. anomalus to degrade gliadins during wheat flour fermentation [ 29 ]. A similar hydrolysis profile of all gliadins was seen, but 48 h of fermentation was necessary to achieve a degradation degree of 20%, ~2-fold lower than that obtained with the yeast strain W. anomalus ME1 at 24 h. Unlike our work, Sakandar et al (2019) [ 29 ] detected oligopeptides and amino acids from gliadin hydrolysis since they used RP-HPL. In the same position, the authors achieved almost total gliadin hydrolysis when the yeast W. anomalus QAUWA03 and the Enterococcus mundtii QAUSD01 were used to ferment wheat dough.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, other authors have also reported the ability of W. anomalus to degrade gliadins during wheat flour fermentation [ 29 ]. A similar hydrolysis profile of all gliadins was seen, but 48 h of fermentation was necessary to achieve a degradation degree of 20%, ~2-fold lower than that obtained with the yeast strain W. anomalus ME1 at 24 h. Unlike our work, Sakandar et al (2019) [ 29 ] detected oligopeptides and amino acids from gliadin hydrolysis since they used RP-HPL. In the same position, the authors achieved almost total gliadin hydrolysis when the yeast W. anomalus QAUWA03 and the Enterococcus mundtii QAUSD01 were used to ferment wheat dough.…”
Section: Discussionsupporting
confidence: 93%
“…Recent reports provide data on the contribution of some yeasts to the degradation of immunogenic wheat proteins when co-inoculated with LAB [ 28 , 29 ]. However, no yeasts performed proteolysis alone have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, this functionality has been associated with some species of sourdough lactobacilli. However, fermentation of some wheat flour varieties by a strain consortium of Enterococcus mundtii QAUSD01 and W. anomalus QAUWA03 acts synergistically in reducing the gliadin content of dough [ 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with those of previous studies reporting protective effects of certain probiotic strains against some gliadin-mediated inflammatory responses. In a previous study, Enterococcus mundtii QAUSD01 and Wickerhamomyces anomalus QAUWA03 were reported to be able to degrade gliadin in various wheat varieties [ 66 ]. Probiotic VSL#3 (Ferring Pharamaceuticals, Milan, Italy), containing Streptococcus thermophilus , L. plantarum , L. acidophilus , L. casei , L. delbrueckii spp.…”
Section: Discussionmentioning
confidence: 99%